ANALISIS KUALITAS PELAYANAN JASA TERHADAP KEPUASAN PELANGGAN PADA CV. AHASS KABUL MOTOR KECAMATAN LEMBEYAN KABUPATEN MAGETAN - Sudarmiani Sudarmiani; Yudha Allan Afri Fiyanto (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
The study describes the quality of service, namely Tangible Responsiveness, Reliability (Reliability) and Assurance (Assurance) against Customer Satisfaction CV. AHASS Kabul Lembeyan Magetan Subdistrict motors. The method in this research is descriptive quantitative method while sampling technique in this research is quota sampling technique that customer in Kabul AHASS Lembeyan Magetan Subdistrict motorcycle that comes to CV. AHASS when distributing questionnaires were 30 respondents. Collecting data using questionnaires, documentation. Analysis of data using linear regression analysis. The results showed that the quality of service on the CV. AHASS Kabul Motor Magetan Subdistrict Lembeyan well. It can be seen from the results of the analysis with the amount of data as much as 30 customers results above the average value (62) as many as 17 customers or 57% below average, while as many as 13 or 43%. Customers CV. AHASS Kabul Motor Lembeyan Magetan satisfied with the services that have been received. It can be seen from the results of the analysis with the amount of data as much as 30 customers angketnya value customers results above average above average (42.90) as many as 18 or 60% of customers while below average as many as 12 customers or 40%.